Smart Integrated Payment System for Public Transportation in Jakarta - Harco Leslie Hendric Spits Warnars; Yulia Lanita; Andhika Prasetyo; Richard Randriatoamanana (Institute of Advanced Engineering and Science, 2017)
Jakarta has many types of public transportation such as Kereta Rel Listrik (KRL), Transjakarta, taxi, angkot, metromini, mikrolet, bajaj, ojek, etc. But, there are some problems that happen in public transportation where the people don’t want to use public transportation and choose to use private transportation that cause more traffic in Jakarta. The problems of public transportation are in the facility which is still inappropriate, unclear information, uncomfortable, bad accessibility of public transportation which take more time to reach the destination, more complicated than taking the private transportation, and about the society, people don’t want to be labeled as low-class level. This paper is representing how to make the better system for public transportation in Jakarta with smart integrated payment system. Aim of this system is to encourage people to use public transportation rather than private transportation. The payment system that proposed are using smartphone application by scanning the QR Code or using smart card. User can easily pay through application by scanning QR code to pay the public transportation. The proposed of this smart integrated payment system will have opportunity as profit when collaborate with business when they can advertise their business and get customer from our user.